The Dynamic Correlations Between Mass Media News and New Media News in Stock Market - Zhang, Zuochao; Zhang, Yongjie; Shen, Dehua (Frontiers in Physics, 2020)
In this paper, we examine the dynamic correlations between mass-media news and new-media news as well as their reprints in the Chinese stock market. We mainly find that: (1) there is a significant positive correlation between the four types of news and the correlation between reprints and their congener media news is stronger; (2) both the mass-media news and new-media news have significant positive autocorrelation. The new-media news and the reprints rely more on mass-media news. (3) both mass-media news and new-media news will make a positive response to the corporate events, but the reaction of new-media news including the new-media reprints is stronger than mass-media; (4) the results of dynamic correlation analysis indicate that there is a significant correlation between the four types of news over time. The correlation between mass-media news and new-media news is stronger when the stock market performs well. We attribute these results to the symbiotic relationship between mass media and new media in the Chinese stock market, where mass media devotes to provide original news with high quality and new media transfers these numbers of news to more readers to attract more attention and discussion.